PENGARUH PENDAPATAN ASLI DAERAH (PAD), DANA ALOKASI UMUM (DAU), DAN DANA BAGI HASIL (DBH) TERHADAP BELANJA MODAL PADA PEMERINTAH DAERAH (STUDI KASUS PADA DINAS KEUANGAN SEEKS KARESIDENAN SURAKARTA) - Nadia Fira Arfiyanti; Suharno Suharno; Bambang Widarno (Universitas Slamet Riyadi, 2020)
The purpose of this study was to examine the effect of local revenue(PAD), general allocation funds (DAU), and revenue sharing (DBH) on capitalexpenditures in local governments. This study uses a sample of non-probabilitysampling with saturated sampling technique so that it gets a sample at theDepartment of Finance of the entire Surakarta Residency. The samples in thisstudy were 7 regions covering 1 Praja City (Surakarta) and 6 districts(Karanganyar, Sragen, Wonogiri, Sukoharjo, Klaten and Boyilali) using agencytheory. The type of data used is secondary data. The results of this study indicatethe significance value of Regional Original Income (PAD) of 0.001 <0.05, it canbe explained that PAD has a significant effect on capital expenditure. Thesignificance value of the General Allocation Fund (DAU) of 0.006 <0.05, it isexplained that the DAU has a significant effect on capital expenditure. Thesignificance value of Revenue Sharing (DBH) is 0.429> 0.05, it can be explainedthat DBH has no effect on capital expenditure. The coefficient of determinationshows an Adjusted R Square of 0.332, the effect of the independent variables,namely Regional Original Income (PAD), General Allocation Fund (DAU), andProfit Sharing Fund (DBH) on Capital Expenditure by 33.2% while the rest(100%) -33.2%) = 66.8% influenced by other variables not studied.